(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: Ropivacaine had clinical advantages over Bupivacaine with respect to cardiac toxicity and motor block and it was suitable for epidural caecerian section. This study was set-up to compare epidural ropivacaine with fentanyl with Bupivacaine / Fentanyl mixture in LSCS surgeries. Method: Out of 90 patients 45 received 10 mg hyperbaric Bupivacaine with 20 microgram fentanyl and 45 (group RF) received 15 mg hyperbaric Ropivacaine with 20 microgram fentanyl Hemodynamic parameters sensory and motor blockade APGAR score were compared in both groups. Results: Demographic profile i.e., Weight, Height BMI Duration of surgery was same in both groups (p>0.001 was insignificant) were motor and sensory blockades highly significant (p<0.001). VAS scores at 4 hours, 6 hours and 8 hours had significant p value (p<0.001). Apgar score at 1 minute was also highly significant (p<0.005). Conclusion: In the present study it was proved that, Hyperbaric Ropivacaine with fentanyl is a better alternative to hyperbaic Bupivacaine with fentanyl in LSCS patients of c-section.